Problems of improvement in dental care among the residents of industrial district - Ulitooskiy, S. B.; Yaremenko, A. N.; Kalynina, O. V.; Aleskeroo, D. Sh (Uchenye zapiski (Sankt-Peterburgskiĭ gosudarstvennyĭ medit͡s︡inskiĭ universitet im. akad. I.P. Pavlova), 2014)
This review introduces readers to the problems of improvement in dental care among the residents of industrial district in megalopolis and the main methods of prevention of dental diseases. The presented data demonstrate the features of dental status of population in industrial district in megalopolis. The article describes the basic ways of prevention of dental diseases and the rules of oral hygiene among the population.